Evaluating the effects of massed and distributed practice on acquisition and maintenance of tacts and textual behavior with typically developing children. Issue 1 (6th November 2014) - Haq, Shaji S.; Kodak, Tiffany
<x xml:space="preserve">Abstract</x> This study evaluated the effects of massed and distributed practice on the acquisition of tacts and textual behavior in typically developing children. We compared the effects of massed practice (i.e., consolidating all practice opportunities during the week into a single session) and distributed practice (i.e., distributing all practice opportunities across 4 sessions during the week) on the acquisition of textual behavior in English, tacting pictures of common nouns in Spanish, and textual behavior in Spanish using an adapted alternating treatments design embedded within a multiple probe design. We also examined correct responding during probes that (a) excluded prompts and reinforcement and (b) occurred 48 hr after training each week. The results indicated that distributed practice was the more efficient training format. Maintenance data collected up to 4 weeks after training also indicated that the participants consistently displayed higher levels of correct responding to targets that had been trained in distributed format. We discuss implications for practice and potential areas for future research.